Growth-friendly fiscal rules? Safeguarding public investment from budget cuts through fiscal rule design - Martín Ardanaz; Eduardo A. Cavallo; Alejandro Izquierdo; Jorge Puig (Inter-American Development Bank (IDB), 2020)
We show that some types of fiscal rules can mitigate the well-known procyclical bias in public capital expenditures. Past research has found that fiscal adjustment episodes coincide with large public investment cuts, a pattern we also document in a sample of 75 advanced and emerging economies during 1990-2018. However, we find that the behavior of public investment during fiscal consolidations differs significantly depending on fiscal rule design. Fiscal rules can be flexible, meaning that they include mechanisms to accommodate exogenous shocks (e.g., cyclically adjusted fiscal targets, well-defined escape clauses, and differential treatment of investment expenditures) or rigid, meaning they establish numerical limits on fiscal aggregates without taking into account flexible features. We find that in countries with either no fiscal rule or with a rigid fiscal rule, a fiscal consolidation of at least 2 percent of GDP is associated with an average 10 percent reduction in public investment. Under flexible fiscal rules, the negative effect of fiscal adjustments on public investment vanishes. These results hold after controlling for possible endogeneity bias in the estimations. We show that by reducing procyclical biases in public investment, flexible fiscal rules can add a growth-enhancing dimension to fiscal sustainability concerns that have typically been the focus of fiscal rules in the past.
Keywords: E32; E60; H12; H50; H54; 330; fiscal rules; public investment; fiscal consolidations; spending cyclicality